Design of a functional mayonnaise enriched with Omega-3 from Sacha Inchi (Plukenetia Huayllabambana) Oil and Chia (Salvia Hispanica L.) mucilage N.I. ONE † - Micali Morales, Mateo Jesus (2025)
This research work focuses on the development of a plant-based mayonnaise (PBM) using Sacha Inchi seeds (Plukenetia huayllabambana) and chia seed mucilage (Salvia hispanica L.), in response to the growing demand for healthier alternatives to traditional mayonnaise. The research question posed is how the incorporation of chia mucilage can replace egg yolk in the formulation of mayonnaise while maintaining similar sensory and nutritional characteristics. The main objective of the study was to evaluate different formulations of PBM, varying the content of chia mucilage (between 1% and 3%) and the water content (43% to 45%), as well as other ingredients such as salt, oil, pepper, and lemon juice. The aim was to determine the emulsion stability, omega-3 content, rheological properties, and physicochemical characteristics of the formulations. The results showed that the formulation with 3% chia mucilage was the most optimal, achieving an emulsion stability of 98.56% and an omega-3 fatty acid content of 55.36% per 100 g of fat, compared to the 0.27% found in traditional mayonnaise. Additionally, this formulation exhibited a high phenolic content and antioxidant activity, highlighting its potential as a nutritious and healthy alternative. The importance of this research lies in its contribution to the creation of healthier food products that address concerns about nutrition and well-being, while also providing a viable option for consumers seeking plant-based alternatives.